Awareness women of childbearing age on early detection cervical cancer: a scoping review - Siti Rukmana; Dewi Rokhanawati; Nurul Kurniati (Universitas 'Aisyiyah Yogyakarta, 2021)
Cervical cancer is caused by HPV acquired by sexual intercourse. Women know that screening is done to detect cervical cancer early. The purpose of this review is to determine the awareness of early detection of cervical cancer in women of childbearing age. Scoping Review by Arksey and O'Malley. Date based are Wiley, Pubmed, Proquest and EBSCO. 9 articles were reviewed by JBI. The results revealed the factors that influence women for early detection types of cervical cancer form of knowledges and education, good knowledge can generate women's awareness of early detection, health promotion and socialization from healthcare proffessionals is very influential.